2014
DOI: 10.1039/c4ra02416h
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances and applications of Glaser coupling employing greener protocols

Abstract: Recent developments in Glaser coupling catalysed by copper(i) is discussed in the review with emphasis on its application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
93
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(95 citation statements)
references
References 108 publications
0
93
0
Order By: Relevance
“…Such reactions provide important steps in a wide range of synthetic strategies for the production of, for example, fine chemicals, carbon rich materials relevant to molecular recognition, and yet others with interesting electronic and optical properties. 2 Subsequently, Hay showed that use of a Cu(I) salt with an amine solvent in the presence of O2 enabled facile homocoupling of terminal alkynes 3 whilst by working in an H2 atmosphere, Elangovan et al showed that exclusion of O2 actually inhibited Hay coupling. 4 Despite extensive investigation, uncertainties remain concerning the mechanism of the homogeneous reaction, in particular in regard to the role of the role of gaseous oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Such reactions provide important steps in a wide range of synthetic strategies for the production of, for example, fine chemicals, carbon rich materials relevant to molecular recognition, and yet others with interesting electronic and optical properties. 2 Subsequently, Hay showed that use of a Cu(I) salt with an amine solvent in the presence of O2 enabled facile homocoupling of terminal alkynes 3 whilst by working in an H2 atmosphere, Elangovan et al showed that exclusion of O2 actually inhibited Hay coupling. 4 Despite extensive investigation, uncertainties remain concerning the mechanism of the homogeneous reaction, in particular in regard to the role of the role of gaseous oxygen.…”
Section: Introductionmentioning
confidence: 99%
“… The representative heterogeneous catalysts covered Amberlyst A‐21 supported CuI, CuNPs@ZnO–PTh, CuO/Fe 2 O 3 NPs, nano Cu 2 O–ZnO . No matter A 3 or KA 2 couplings, a terminal alkyne is a common reactant partner which occasionally produces the Glaser‐Hay homocoupling by‐product in the presence of some kind of metal catalytic systems resulting in decreasing the yield of the propargylamine product . To address these issues, the decarboxylative coupling reaction of an aryl aldehyde, an alkynyl carboxylic acid, and an amine (decarboxylative A 3 ) is a practical variant.…”
Section: Introductionmentioning
confidence: 99%
“…[6-10] The reaction is usually performed with Cu or Pd as the catalyst and organic base under heated condition in organic solvents, which are not environmentally friendly. [11][12][13][14][15] An environmentally friendly, efficient and solvent-free method for the terminal alkyne homocoupling reaction was reported in 2010. [7] The terminal alkyne can be totally transformed at 60℃ after 6 h with catalytic amounts of Cu(II) salt and base.…”
Section: Introductionmentioning
confidence: 99%